2007
DOI: 10.1124/jpet.107.125435
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Urothelial Transient Receptor Potential Vanilloid 4 by 4α-Phorbol 12,13-Didecanoate Contributes to Altered Bladder Reflexes in the Rat

Abstract: The ion channel transient receptor potential vanilloid (TRPV) 4 can be activated by hypo-osmolarity, heat, or certain lipid compounds. Here, we demonstrate expression of functional TRPV4 protein in the urothelium lining the renal pelvis, ureters, urinary bladder, and urethra. Exposure of cultured rat urothelial cells from the urinary bladder to the TRPV4-selective agonist 4␣-phorbol 12,13-didecanoate (4␣-PDD) promoted Ca 2ϩ influx, evoked ATP release, and augmented the ATP release evoked by hypo-osmolarity. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
144
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(150 citation statements)
references
References 43 publications
4
144
2
Order By: Relevance
“…Recent research has identified TRPV4 as an important regulator of normal bladder function (12)(13)(14)(15)(16)25), but its involvement in the development of cystitis and the associated changes in bladder function was unknown. In this article, we show that the development of reduced functional bladder capacity and pollakisuria after cyclophosphamide treatment is strongly impaired in Trpv4 −/− mice, despite clear signs of severe hemorrhagic cystitis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has identified TRPV4 as an important regulator of normal bladder function (12)(13)(14)(15)(16)25), but its involvement in the development of cystitis and the associated changes in bladder function was unknown. In this article, we show that the development of reduced functional bladder capacity and pollakisuria after cyclophosphamide treatment is strongly impaired in Trpv4 −/− mice, despite clear signs of severe hemorrhagic cystitis.…”
Section: Discussionmentioning
confidence: 99%
“…The physiological role of TRPV4 and which of these possible activating stimuli is physiologically relevant remain unknown. TRPV4 is highly expressed in renal nephron and in hypothalamus, and through its osmosensory properties may play a role in regulating body fluids (2,42), but is also expressed in bladder epithelium, where it may play a role in bladder voiding (9,43) and in sensory neurons, where roles both in detection of strong mechanical stimuli (5) and sensation of warm temperatures (10) have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…TRPV4 is a member of the transient receptor potential vanilloid subfamily of TRP 2 channels, and like other members of this subfamily, it is a polymodal receptor activated by a wide variety of stimuli. TRPV4 is strongly expressed in kidney and is activated by hypotonicity, which has led to the suggestion that TRPV4 is an osmosensor important in regulating body fluid levels (2,(5)(6)(7)(8)(9). However, TRPV4 is also activated by innocuous heat with a threshold of Ͼ27°C (6,10,11), by the phorbol ester 4␣-phorbol 12,13-didecanoate (12,13), by low pH (14), by endocannabinoids and arachidonic acid metabolites (15,16), by the active compound, bisandrographolide A, of Andrographis paniculata, a Chinese herbal plant (17), and by nitric oxide (18).…”
mentioning
confidence: 99%
“…When the intravesical pressure of urinary bladder or the degree of urothelium distention increases, ATP is released from urothelial cells (Ferguson et al 1997) and activates purinergic receptors expressed in nearby nerve terminals within the urothelium, carrying the information to the central nervous system (Birder 2005). According to previous physiological experiments, TRPV4, a Ca 21 -permeable stretch-activated cation channel, is expressed in rat and mouse urothelial cells (Birder et al 2007;Gevaert et al 2007). The activation of TRPV4 by hypotonic stimuli or 4a-phorbol 12,13-didecanoate (4a-PDD), a TRPV4 agonist, induces significant increases in [Ca 21 ] i in rat urothelial cells, leading to ATP release (Birder et al 2007).…”
mentioning
confidence: 99%